SOCIAL STUDIES TEACHERS‟ QUEST FOR A VERTICALLY-ARTICULATED CAREER PATH - Inocian, Reynaldo B.; Hermosa, Eden M. (European Scientific Journal, ESJ, 2014)
Nelson Mandela once said, “Education is the only weapon we can use to change the world”. Hence, today‘s ―educational policies aim atmaking education more effective‖ (Uusiautti & Maatta, 2013) andconsequently, ―seeing teaching as a continuous process of learning‖(Stockard, 2001) can make education stronger. In order to be brandedglobally competitive, educators are pushed to be important prime movers ofchange for social transformation. This study sought to find out the careerpaths of Social Studies teachers who graduated with Master‘s degrees inEducation from 2000 to 2013. Their profile, motivational factors, andbenefits acquired were investigated through purposive sampling. A mixedmethod of both quantitative and qualitative approaches was used in the studywith a descriptive survey through a researcher-made-questionnaire in thecollection of data. To facilitate the data collection, online/personal interviewsand analysis of the curriculum vitae of respondents were used. The studyrevealed a diverse demographic profile, different motivational factors, andvaried significant insights. The attainment of a master‘s degree in socialstudies had contributed to a lot of benefits that led to a vertically-articulatedcareer path that ensures professional quality and sterling professionalcommitment.